Pathways between foodways and wellbeing for First Nations Australians - Kate Anderson; Elaina Elder-Robinson; Megan Ferguson; Bronwyn Fredericks; Simone Sherriff; Michelle Dickson; Kirsten Howard; Gail Garvey (BMC, 2024)
Abstract Background Supporting the health and wellbeing of Aboriginal and Torres Strait Islander peoples (hereafter respectfully referred to as First Nations peoples) is a national priority for Australia. Despite immense losses of land, language, and governance caused by the continuing impact of colonisation, First Nations peoples have maintained strong connections with traditional food culture, while also creating new beliefs, preferences, and traditions around food, which together are termed foodways. While foodways are known to support holistic health and wellbeing for First Nations peoples, the pathways via which this occurs have received limited attention. Methods Secondary data analysis was conducted on two national qualitative datasets exploring wellbeing, which together included the views of 531 First Nations peoples (aged 12-92). Thematic analysis, guided by an Indigenist research methodology, was conducted to identify the pathways through which foodways impact on and support wellbeing for First Nations peoples. Results and conclusions Five pathways through which wellbeing is supported via foodways for First Nations peoples were identified as: connecting with others through food; accessing traditional foods; experiencing joy in making and sharing food; sharing information about food and nutrition; and strategies for improving food security. These findings offer constructive, nationally relevant evidence to guide and inform health and nutrition programs and services to harness the strengths and preferences of First Nations peoples to support the health and wellbeing of First Nations peoples more effectively.